PERBANDINGAN PENINGKATAN KADAR KALIUM PASIEN LANSIA DENGAN HIPERTENSI YANG DITERAPI ACE-I DANARB DI RSUP FATMAWATI PADA TAHUN 2017-2019 - Almerveldy Azaria Dohong (2020)
Hypertension is a common disease in the elderly due to various factors. ACE-I and ARB are the first line antihypertensives treatment based on JNC-8 guidelines. Both of these antihypertensives have side effects in the form of increased blood potassium levels, all while the elderly is susceptible to impaired electrolyte balance. The purpose of this study was to compare the increase in potassium levels in elderly patients treated with ACE-I and ARB. This research was an analytic observational study with crosssectional design, conducted at Fatmawati General Hospital. The sample was the medical record data of 72 elderly patients aged 60-82 years. There were 39 patients taking ARB antihypertensive and 33 people taking ACE-I. The sampling technique used was consecutive sampling method. Potassium levels in the elderly who had been using ACE-I antihypertensive increased by an average of 0.49 mmol / L while those who had been using ARB increased by an average of 0.46 mmol / L from the initial potassium level. The independent T-test results showed that there was no significant difference in the increase in potassium levels between the use of both antihypertensives (p value = 0.716) in elderly patients with hypertension who were treated with ACE-I and ARB in Fatmawati General Hospital in 2017 - 2019.